Elevated hepatic lipase activity and low levels of high density lipoprotein in a normotriglyceridemic, nonobese Turkish population - Thomas P. Bersot; Gloria Lena Vega; Scott M. Grundy; K. Erhan Palaoğlu; Pamir Atagündüz; Sinan Özbayrakçi; Oryal Gökdemir; Robert W. Mahley (Journal of Lipid Research, 1999)
Low levels of high density lipoprotein cholesterol (HDL-C) are associated with increased risk of coronary heart disease and, in the United States, are often associated with hypertriglyceridemia and obesity. In Turkey, low HDL-C levels are highly prevalent, 53% of men and 26% of women having HDL-C levels <35 mg/dl, in the absence of hypertriglyceridemia and obesity. In this study to investigate the cause of low HDL-C levels in Turks, various factors affecting HDL metabolism were assessed in normotriglyceridemic Turkish men and women living in Istanbul and in non-Turkish men and women living in San Francisco. Turkish men and women had significantly lower HDL-C levels than the San Francisco men and women, as well as markedly lower apolipoprotein A-I levels (25 and 39 mg/dl lower, respectively). In both Turkish and non-Turkish subjects, the mean body mass index was <27 kg/m2, the mean triglyceride level was <120 mg/dl, and the mean total cholesterol was 170–180 mg/dl. The mean hepatic triglyceride lipase activity was 21% and 31% higher in Turkish men and women, respectively, than in non-Turkish men and women, and remained higher even after subjects with a body mass index >50th percentile for men and women in the United States were excluded from the analysis. As no dietary or behavioral factors have been identified in the Turkish population that account for increased hepatic triglyceride lipase activity, the elevation most likely has a genetic basis. —Bersot, T. P., G. L. Vega, S. M. Grundy, K. E. Palaoğlu, P. Atagündüz, S. Özbayrakçi, O. Gökdemir, and R. W. Mahley. Elevated hepatic lipase activity and low levels of high density lipoprotein in a normotriglyceridemic, nonobese Turkish population. J. Lipid Res.40: 432–438.